Self‐control protects Tibetan adolescent orphans from mental problems: A mediating role of self‐esteem. Issue 2 (14th February 2022) - Zheng, Miao; Peng, Kaiping; Yan, Wei; Lin, Yujing; Ni, Zijun; Zhang, Peng
Abstract: Introduction: Orphans are usually adopted by eligible families or raised by the government and organizations mutually. Although their basic needs are taken care of, the absence of parents in life makes orphans face higher risks of mental health problems, such as anxiety and depression, leading to lower levels of self‐esteem and happiness. Previous studies have shown that self‐control may have an effect on improving self‐esteem; thus, it could become a way to protect mental health. Building on the structural equation model, the current study tested the possible effects of self‐control on levels of self‐esteem and mental problems among Tibetan orphans. Methods: Participants were 143 adolescents from age 16 to 22 years ( M age  = 18.77, 54.8% female) from an institutionalized orphanage in Tibet and they completed questionnaires measuring self‐esteem, self‐control, and clinical symptoms (Symptom Checklist‐90‐Revised). Results and conclusions: Self‐control was negatively associated with psychological illness through improved self‐esteem. The present study suggested that self‐control was a protective factor for the mental health of adolescent orphans through influencing the levels of self‐esteem. Limitations and future directions were discussed.